Enhancing employee performance through structured job training: Evidence from Puskesmas Pademangan, Jakarta - Prisia, Epin; Efkelin, Ria; Mailintina, Yurita (Majalah Kesehatan Indonesia, 2024)
This study explores the relationship between job training and employee performance at the Puskesmas of Pademangan District, North Jakarta. The study aims to examine how various components of job training, including training objectives, instructors, and materials, affect employee performance. Using a quantitative approach with a descriptive method, data were collected from 192 Puskesmas employees using a structured questionnaire. The results revealed a significant positive relationship between job training and employee performance. Specifically, employees who rated their training programs as "good" demonstrated higher levels of job performance. Statistical analysis using the chi-square test showed that all dimensions of training (objectives, instructors, and materials) were significantly associated with improved performance. These findings support existing theories on the importance of well-structured job training in enhancing employee productivity and service quality. The study concludes that ongoing improvements in training content and delivery methods will further enhance employee performance at Puskesmas. Recommendations for Puskesmas administrators include regular evaluation of training programs and tailored development initiatives to meet specific employee needs. Future research should investigate the long-term impacts of training and explore potential moderating factors such as organizational culture and employee motivation.